2009
DOI: 10.1159/000251712
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of Androgen Insensitivity Syndrome

Abstract: Androgen insensitivity syndrome (AIS) (OMIM 300068) is an X-linked recessive genetic disorder with an XY karyotype that is caused by androgen receptor (AR) defects. We report a prenatal diagnosis case with clinical and molecular findings. The fetal phenotype was female, moreover the autopsy revealed the presence of abdominal testes confirmed by histopathological examination. The AR gene molecular analysis performed on the fetal DNA showed the presence of a c.2493C>T change in exon 4. The single nucleotide chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…Previous studies reported that more than half of individuals with CAIS presented with inguinal hernia and the incidence of CAIS in girls undergoing hernia repair was 1% [6,12]. Third, more recently fetuses or neonates are being diagnosed prenatally or immediately after birth due to a mismatch between fetal karyotype and external genitalia [13][14][15][16]. Individuals with ambiguous genitalia are recognized at birth, but individuals with complete sex reversal, the 46,XY karyotype and complete female external genitalia are usually overlooked at birth and receive diagnosis during adolescence based on primary amenorrhea or delayed puberty.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that more than half of individuals with CAIS presented with inguinal hernia and the incidence of CAIS in girls undergoing hernia repair was 1% [6,12]. Third, more recently fetuses or neonates are being diagnosed prenatally or immediately after birth due to a mismatch between fetal karyotype and external genitalia [13][14][15][16]. Individuals with ambiguous genitalia are recognized at birth, but individuals with complete sex reversal, the 46,XY karyotype and complete female external genitalia are usually overlooked at birth and receive diagnosis during adolescence based on primary amenorrhea or delayed puberty.…”
Section: Discussionmentioning
confidence: 99%
“…Recent diagnostics modalities offer detection of CAIS earlier than it was in the past: diagnostic is possible in utero for a female phenotype is visible at 16 th weeks' gestation by two-dimensional or four-dimensional sonography and can be compared with karyotype analysis [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal diagnosis has been reported previously with discrepancy between fetal external genitalia noted at the time of ultrasound examination and the results of sex chromosome analysis following amniocentesis 1 . We present a case of prenatal diagnosis of AIS with discrepancy between fetal external genitalia seen during ultrasound examination and the results of cell-free fetal DNA (cffDNA) testing.…”
Section: Prenatal Diagnosis Of Androgen Insensitivity Syndrome Using mentioning
confidence: 98%